ANALISIS GAYA HIDUP SEHAT PADA WANITA YANG AKTIF BEROLAHRAGA - Manalu, Nimrot; Rahmahani, Aisyah; Vellina, Fifi; Adzmi, Khairul; Arif, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze healthy lifestyles among women who actively engage in sports and to identify the factors influencing the implementation of healthy living patterns in daily life. The research employed a descriptive qualitative approach involving 80 women who regularly exercised at least three times a week as research subjects. Data collection techniques included observation, semi-structured interviews, and documentation. The data were analyzed using descriptive qualitative techniques through data reduction, data presentation, and conclusion drawing. The results showed that the majority of respondents were aged 25–35 years, had Diploma/Bachelor educational backgrounds, and were predominantly private employees. Most respondents exercised three times a week, with gym or fitness activities being the most common type of exercise. In addition, the majority of respondents had implemented healthy eating patterns, although irregular sleeping patterns were still found due to daily activities and work demands. The study also revealed that social media had an influence on women’s healthy lifestyles, particularly in shaping perspectives regarding health and physical appearance. Therefore, healthy lifestyles among women who actively exercise are influenced not only by physical activity but also by eating habits, rest patterns, social environment, and digital media.